MENELAAH KEBERHASILAN SISTEM PENDIDIKAN SEKOLAH DASAR DI JEPANG UNTUK DITERAPKAN DI INDONESIA - Savitri, Dewinta Aulia; Susanti, LR Retno; Safitri, Erna Retna; Gulo, Fakhili (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Indonesia and Japan have the same focus on educational goals, which is to focus on cultivating character education starting from elementary school education. However, Indonesia is currently ranked 72nd out of 77 countries when compared to Japan. Indonesia's education system at the primary school level requires special treatment and greater attention. Comparing Indonesia with a country with the best education system like Japan, is a systemic step to create high-quality education. Students in Japan are taught moral and ethical education starting from the first 3 years of elementary school. Approaches, methods, assessments, activeness, and the use of technology are crucial for the success of elementary school education in Japan. The education system at the elementary school level provides great potential to be offered to Indonesia.